2018
DOI: 10.3892/ijmm.2018.3789
|View full text |Cite
|
Sign up to set email alerts
|

Inducible HSP70 antagonizes cisplatin‑induced cell apoptosis through inhibition of the MAPK signaling pathway in HGC‑27 cells

Abstract: Inducible heat shock protein 70 (HSP70; also known as HSPA1 or HSP72) is implicated in cancer. As a stress-inducible heat shock protein, HSP70 is highly expressed in a variety of cancers and correlates with metastasis, chemotherapy resistance and tumor prognosis. The present study demonstrated that suppression of HSP70 through the specific inhibitor pifithrin-µ or by HSP70 knockdown enhanced cisplatin-induced apoptosis in HGC-27 gastric cancer cells. By contrast, upregulation of HSP70 through transfection of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The present study demonstrated that HSP70 was elevated by CSE treatment in the mitochondrial fraction of HL-60 cells exposed to cisplatin. These results are supported by previous reports showing reduction of HSP70 enhances cisplatin-induced apoptosis in HGC-27 gastric cancer cells and A529 lung adenocarcinoma cells, as well as accumulation of HSP70 inhibits heat shock-induced apoptosis in HL-60 cells [57][58][59]. In relation to these findings, it is of interest that we observed that cisplatin-induced release of cytochrome c from mitochondria and compromised mitochondrial function were reversed by CSE.…”
supporting
confidence: 92%
“…The present study demonstrated that HSP70 was elevated by CSE treatment in the mitochondrial fraction of HL-60 cells exposed to cisplatin. These results are supported by previous reports showing reduction of HSP70 enhances cisplatin-induced apoptosis in HGC-27 gastric cancer cells and A529 lung adenocarcinoma cells, as well as accumulation of HSP70 inhibits heat shock-induced apoptosis in HL-60 cells [57][58][59]. In relation to these findings, it is of interest that we observed that cisplatin-induced release of cytochrome c from mitochondria and compromised mitochondrial function were reversed by CSE.…”
supporting
confidence: 92%
“…accumulating evidence has indicated an important role of the Pi3K/aKT signaling pathway in osteosarcoma (11,34,35); Pi3K/aKT signaling modulates the proliferation, invasion, migration and apoptosis of osteosarcoma cell lines (36)(37)(38)(39)60). Previous studies revealed that alantolactone is a specific inhibitor in several diseases via the Pi3K/aKT signaling pathway (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway, known as a cascade of protein kinases, is closely associated with the tumorigenesis in multiple malignancies. [50][51][52] The activation of MAPK pathway could stimulate various oncogenic systems including EMT, which transferred epithelial characteristics into mesenchymal phenotype, finally leading tumors getting migratory and invasive features. 53 Consistently, our study also demonstrated that overexpression of CIC inhibited the proliferative and invasion of RCC cells in vivo through suppressing the activation of MAPK pathway, which indicated that MAPK pathway might be involved in the regulation of miR-106b/CIC axis during proliferation and metastasis in RCC progression.…”
Section: Discussionmentioning
confidence: 99%